Protection from Disulfide Stress by Inhibition of Pap1 Nuclear Export in Schizosaccharomyces pombe. Issue 3 (4th September 2018) - Chen, Yan; Zhang, Yan; Dong, Zhicheng; Ow, David W
Abstract: Appropriate subcellular localization of regulatory factors is critical for cellular function. Pap1, a nucleocytoplasmic shuttling transcription factor of Schizosaccharomyces pombe, is redox regulated for localization and antistress function. In this study, we find that overproduction of a peptide conjugate containing the nuclear export signal of Oxs1, a conserved eukaryotic protein that, along with Pap1, regulates certain diamide responsive genes, can retain Pap1 in the nucleus before stress by competing for nuclear export. The nuclear retention of Pap1 upregulates several drug resistance genes to prime the cells for higher tolerance to disulfide stress. Overproduction of Oxs1 also upregulates these same genes, not by competing for export but by binding directly to the drug resistance gene promoters for Pap1-mediated activation. Of medical relevance is that this may suggest a gene therapy approach of using nuclear export signal conjugates to suppress the nuclear export of biomolecules.